2013
DOI: 10.1007/s11596-013-1063-5
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of salicylates for type 2 diabetes mellitus

Abstract: The aim of this study was to assess the effects and safety of salicylates on type 2 diabetes mellitus (T2DM). We searched six databases (Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, CBM, CNKI and VIP) for all randomized controlled trials (RCTs) and self-control studies which investigated the effects of salicylates on T2DM. We included 34 RCTs and 17 self-control studies involving 13 464 patients with T2DM. It was demonstrated that salicylates had obvious effects on several parameters for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Several trials in the last decade were conducted to determine the effect of aspirin in diabetes pathogenesis [ 47 53 ]. A recent meta-analysis conducted by Fang and colleagues [ 54 ] concluded that the anti-diabetic effect of salicylates is in a dose-dependent manner. High doses of salicylates may have beneficial effects on reducing FPG, HbA1c level and increasing fasting insulin concentration, and may also have some positive effects on lipidemia and inflammation-associated parameters for patients with T2DM, without severe adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several trials in the last decade were conducted to determine the effect of aspirin in diabetes pathogenesis [ 47 53 ]. A recent meta-analysis conducted by Fang and colleagues [ 54 ] concluded that the anti-diabetic effect of salicylates is in a dose-dependent manner. High doses of salicylates may have beneficial effects on reducing FPG, HbA1c level and increasing fasting insulin concentration, and may also have some positive effects on lipidemia and inflammation-associated parameters for patients with T2DM, without severe adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent hyperglycemia and a chronic inflammatory environment lead to oxidation-mediated stress and injury and also alter insulin sensitivity by triggering different key steps in the insulin-signaling pathway [ 22 ]. Cyclooxygenase-2 inhibitors, members of the non-steroidal anti-inflammatory drug class, have been shown the ability to alleviate the augmented inflammatory responses in several models of diabetes [ 23 , 24 , 25 ]. However, their adverse effects on targets, including impaired renal perfusion and its function, peptic ulcers, and enhanced risk of myocardial infarction, contribute to limited use of these drugs for clinical prevention/treatment of T2DM [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…After that, additional trials have been reported similar effects that the treatment of sodium salicylate improved glucose homeostasis [87][88][89][90][91][92][93][94]. A recent meta-analysis of salicylates, including sodium salicylate, aspirin (acetylsalicylate), and salsalate (2-[2hydroxybenzoyl]oxybenzoic acid), for T2DM showed that any doses of salicylates reduce glycated hemoglobin (HbA1c) level and that high doses of sodium salicylate (>3000 mg/day) improve fasting plasma glucose level [95].…”
Section: Salicylic Acidmentioning
confidence: 99%